(untitled) (Homoeopathy for All, 2024)
Terms “anxiety” and “nervous” are often used interchangeably, feeling nervous and having an anxiety disorder are two very different things.When anxiety takes center stage in life, even the small task seem mountainous. It becomes a psychological disorder, which requires immediate attention and help. Homoeopathy is a remarkable resource for those dealing with mental health disorders. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of this disorder.